2020
DOI: 10.18632/aging.103390
|View full text |Cite
|
Sign up to set email alerts
|

The Gαh/phospholipase C-δ1 interaction promotes autophagosome degradation by activating the Akt/mTORC1 pathway in metastatic triple-negative breast cancer

Abstract: Lung metastasis (LM) is commonly found in triple-negative breast cancer (TNBC); however, the molecular mechanism underlying TNBC metastasis to lungs remains largely unknown. We thus aimed to uncover a possible mechanism for the LM of TNBC. Here we show that the phosphorylation of Akt and mTORC1 was positively but the autophagy activity was negatively correlated with endogenous Gαh levels and cell invasion ability in TNBC cell lines. Whereas the knockdown of Gαh, as well as blocking its binding with PLC-δ1 by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…It might be important to underline also that the binding of PLCδ1 by TG2 supports autophagosome degradation in MDA-MB-231 cells [90]; therefore, blocking the formation of this complex could have therapeutic implications.…”
Section: Discussionmentioning
confidence: 99%
“…It might be important to underline also that the binding of PLCδ1 by TG2 supports autophagosome degradation in MDA-MB-231 cells [90]; therefore, blocking the formation of this complex could have therapeutic implications.…”
Section: Discussionmentioning
confidence: 99%
“…BKM120, the PI3K inhibitor, exhibited a significant inhibition of tumor growth, with 84% tumor-growth inhibition [123]. Lin et al, 2020 used rapamycin, an inhibitor of mTORC1, to treat metastatic TNBC [124]. In phase II clinical trials (NCT02162719), TNBC patients received paclitaxel i.v.…”
Section: Inhibition Of Egfr Signaling Pathwaymentioning
confidence: 99%
“…It has been shown that BKM120 therapy led to significant tumor growth inhibition in all models, with the percentage of tumor growth inhibition (%TGI) ranging from 35% in the least sensitive model WHIM12 (PTEN-deficient) and 84% in the most sensitive model WHIM4 (PTEN-normal) (22). Lin et al proposed another strategy for using an mTORC1 inhibitor, rapamycin, to combat metastatic TNBC with upregulated Gah, also known as tissue transglutaminase (tTG) or transglutaminase 2 (TG2) (23). Patients from a randomized, double-blind, phase II trial (NCT02162719) received intravenous paclitaxel with or without Akt inhibitor ipatasertib until disease progression or unacceptable toxicity.…”
Section: Pi3k/akt/mtor Inhibitionmentioning
confidence: 99%